Power relations in the finance of infrastructure public-private partnership projects. Issue 7 (October 2022) - Liu, Lucia Xiaoyan; Clegg, Stewart; Pollack, Julien
Highlights: This paper investigates how the dynamics of power relations in SPVs hinder their effectiveness in delivering public infrastructure Public Private Partnership (PPP) projects. Project finance, one of the key elements in PPP projects, play a disproportionate role in the organizational politics of PPP Special Purpose Vehicle (SPV). The dynamics of these organizational politics have a paradoxical effect on SPVs' organisational and managerial agency, affecting PPP performance and benefits realisation. We illustrate how SPVs might improve PPP project performance based on an analysis using resource dependence theory and circuits of power, stressing social as well as system integration. We develop a theoretical model of circuits of power to capture the data and to provide a model for future reform. Abstract: This research investigates the impact of project finance on the ability of Special Purpose Vehicles (SPVs) to deliver infrastructure Public Private Partnership (PPP) projects. The research reports on data that was collected through 46 in-depth interviews with senior executive practitioners involved in PPPs in Australia. Analysis of this data confirms that while SPVs are integral vehicles for PPP integration, organizational power dynamics can generate tensions that restrict SPVs' ability to manage PPP delivery effectively. Control of the key resource of capital, by debt and equity investors, is central in SPV power plays. Improved understanding of power dynamics will help PPPs better achieve benefits through reforms that enhance managerial agency and develop stronger social and system integration, enabling better alignment of the interests of key stakeholders.